Development and acceptability of ViviendoPositivos: A culturally tailored telenovela (soap opera) intervention to improve self-management among Latinos with HIV - Evelyn Iriarte; Natalia Villegas; Samantha Stonbraker; Paul Cook; Maria Jose Baeza; Rosina Cianelli; Christine Toledo; Kristine M. Erlandson; Catherine Jankowski (PLoS ONE, 2025)
Because people with HIV are living longer, there is a growing need for effective health self-management interventions. An urgent gap in care for Latino people with HIV (LWH) is the lack of culturally adapted interventions to support their health information needs. To respond to this need, we developed ViviendoPositivos, a culturally tailored telenovela (soap opera) intervention to promote HIV self-management among LWH. We used a mixed methods approach to gather data for the development of the intervention from 24 Spanish or English-speaking LWHs aged ≥ 18 years. Telenovela vignettes were co-created in collaboration with a community advisory board (CAB), our research team, and a telenovela director. Through focus groups, individual interviews, and a survey, we explored the acceptability of the telenovela vignettes (n = 24 LWH). Participants were mostly male (88%, n = 21), with an average age of 49 years (SD = 12) and living with HIV for 16 years (SD = 12). During the development of ViviendoPositivos, CAB members identified five priority content areas: mental health and social support, HIV knowledge, adherence to antiretroviral treatment, partner communication and negotiation, and healthy aging. Contextual and cultural aspects were also incorporated into the telenovela vignettes. Participants reported high satisfaction with the information and stories presented (92%, n = 22) and mentioned that the topics were relatable. All participants expressed willingness to watch the telenovela with a preference for online streaming via a website. The final product was an HIV self-management telenovela series of five 10-minute filmed episodes that incorporated the ideas and feedback of LWH.